A Two-Dimensional Problem with a Gravitational Field and Inclined Load in the Context of Three Thermoelastic Theories - Alzaerah Aldeeb, (AlQalam Journal of Medical and Applied Sciences, 2025)
A model of the equations of two-dimensional problems is studied in a half space, with Porous material under the effect of gravity and an inclined load in the context of the three theories of Lord–Shulman, Green-Lindsay, and classical-coupled. The inclined load is assumed to be a linear combination of a normal mode and a tangential load. The formulation is performed in the context of the Lord-Shulman and Green-Lindsay theories, as well as the classical dynamical coupled theory. Comparisons are made with the results in different values of the angle of inclination, as well as the absence and presence of gravity.